2008
DOI: 10.1542/peds.2007-2281
|View full text |Cite
|
Sign up to set email alerts
|

Annual Risk of Death Resulting From Short Falls Among Young Children: Less Than 1 in 1 Million

Abstract: The best current estimate of the mortality rate for short falls affecting infants and young children is <0.48 deaths per 1 million young children per year. Additional research is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(58 citation statements)
references
References 157 publications
1
54
1
2
Order By: Relevance
“…52 It has been estimated that the population-based risk of a short fall death for an infant or young child is ,1 per 1 million young children per year. 53 The identification of physical abuse can be difficult. Other than the perpetrator and the child, witnesses to the abuse are uncommon; perpetrators of the abuse infrequently admit to their actions; child victims are often preverbal and may be too severely injured or too frightened to disclose their abuse; and injuries can be nonspecific.…”
Section: Missed Opportunities For Diagnosing Physical Abusementioning
confidence: 99%
See 1 more Smart Citation
“…52 It has been estimated that the population-based risk of a short fall death for an infant or young child is ,1 per 1 million young children per year. 53 The identification of physical abuse can be difficult. Other than the perpetrator and the child, witnesses to the abuse are uncommon; perpetrators of the abuse infrequently admit to their actions; child victims are often preverbal and may be too severely injured or too frightened to disclose their abuse; and injuries can be nonspecific.…”
Section: Missed Opportunities For Diagnosing Physical Abusementioning
confidence: 99%
“…149 Although most household trauma results in minor or no injury, on rare occasion, severe or fatal head injury has been reported. 53 In addition to searching for occult trauma in patients who present with such a history, or in infants and young children who present with unexplained intracranial hemorrhage and/or hypoxic ischemic cerebral injury, consideration of alternate explanations is often required. Investigation by child welfare or law enforcement can also help to distinguish accidental from abusive head injury, and reporting to CPS for investigation in all suspicious cases is advised.…”
Section: Head Injuriesmentioning
confidence: 99%
“…Another study found that the population-based risk of dying after a short distance fall for young children is less than 1 per million per young children per year (47). Many studies have demonstrated a statistically significant worse outcome (for both physical and cognitive functioning) for abusive head trauma patients than for accidental trauma patients (13).…”
Section: Prognosismentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Additionally, a medical history of symptoms suggestive of a bleeding disorder, such as significant bleeding after a circumcision or other surgery, epistaxis, bleeding from the umbilical stump, or excessive bleeding after dental procedures, increases the possibility of a bleeding disorder. Family history of a specific bleeding disorder or ethnicity of a population with higher rates of a certain bleeding disorder (eg, Amish) might necessitate testing for that condition.…”
Section: Assessing the Need For A Laboratory Evaluation For Bleeding mentioning
confidence: 99%
“…Children can suffer ICH, such as a small subdural or an epidural hematoma underlying a site of impact, from a short fall; however, short falls rarely result in significant brain injury. 16 Birth trauma and some medical conditions can also result in ICH in infants. Consultation with a child abuse pediatrician should be considered in complex or concerning cases.…”
Section: Ichmentioning
confidence: 99%